Business Incubator Centers and Their Role in Empowering Micro, Small, and Medium Enterprises in Sidoarjo - Setyawanto, Agus; Hariyadi, Bachtiar; Tontowi; Koroma, Christiana (Jurnal Soeropati, 2023)
Kebonagung Village, a Sukodono District area, is home to a growing number of Micro, Small, and Medium Enterprises (MSMEs) but lacks effective product marketing management. The lack of a Business Incubator Center (BIC) hinders MSMEs from developing their marketing strategies. This study aims to map MSMEs' existing potential and development needs in Kebonagung Village through various BIC networks. The research methodology combines Participatory Rural Appraisal (PRA) and Asset-Based Community Development (ABCD), with the active involvement of MSME actors. The program stages involve field observations, preparation, implementation, and socialization activities. The results show that the existing potential of MSMEs falls into the "micro" category, with a weighted score of 76.23%. The BIC network provides effective support with a "good" rating of 64.21%. The MSME development program has yielded outcomes such as the formation of the "Forum Asosiasi UMKM Bonagung" and opportunities for further collaboration with BIC.